On (not) assembling a market for sustainable energy: heat network infrastructure and British cities. Issue 1 (2nd January 2017) - Webb, Janette; Hawkey, David
ABSTRACT: Energy policies increasingly rely on market instruments to meet societal objectives for climate change mitigation. We explore the application of such instruments in low carbon heat markets. Using a conceptual framework derived from actor network theory and economic sociology, we examine the role of technical-economic models as market devices in two heat network proposals in British cities. Government intermediaries relied on the models to enact the mutual financial and carbon benefits of an area-wide heat market, and to enrol multiple public sector organisations in innovation. In practice, the models produced the opposite response: parties synthesised the modelled cost–benefit calculations into the existing public services market agencement and translated the model numbers ino opportunities to secure competitive advantage for their own organisation. These activities undermined the projected cost and carbon saving logic of the collective actor solution. The findings demonstrate the potent economic agency of market-emulating public finance and competitive procurement instruments in governing such organisational decisions, and indicate the limited traction of a low carbon calculus, which lacked significant political or senior management sponsorship. Questions are posed about the formatting of economic agency suited to securing the common goods of a sustainable society.